IMPORTANT ISSUES OF KNOWLEDGE OF FOREIGN LANGUAGES IN MODERN SOCIETY (American Journal of Research in Humanities and Social Sciences, 2023)
This article examines the role of a foreign language in modern society. Today, theoretical and practical aspects of the need and importance of learning and knowing foreign languages have been analyzed. The practical advantages of knowing and using foreign languages are also considered.